Production Planning and Control - Pradhan , Bibhuti Bhusan (International Journal of Psychosocial Rehabilitation, 2019)
Production planning and control is involved with implementation of the plans, i.e. detailed job scheduling, assignment of workloads to machines (and people), and actual work flow through the system. Production is an organized activity whereby row materials are converted into useful products. Production work is carried out in a broad range of production and service sectors. Production system involves the optimum use of natural resources such as people, energy, machinery, materials and time. Coordinate production planning and monitoring with the different departments: like manufacturing, marketing, distribution, warehouse and other divisions depending on the organizational design. Production preparation and control collects data from marketing departments relating to orders. Production plan is prepared in production planning and control, based on marketing and production data. The business plan gives a clear picture of industrial tools being used for production. The approved development schedule is submitted to the Department of Business. Department of Production produces goods under that plan.